Disease control in aquaculture and the responsible use of veterinary drugs and vaccines: the issues, prospects and challenges - Subasinghe R. (The use of veterinary drugs and vaccines in Mediterranean aquaculture, 2009)
Aquatic animal diseases are the most significant constraint to the development and management of aquaculture worldwide. As aquaculture is growing rapidly and poised to help in bridging the gap in the global supply and demand of aquatic animal food products, management of health and reducing losses due to disease in aquaculture is gaining high priority. One of the key areas of success in managing aquatic animal health in aquaculture has been the development of vaccines. There has been significant progress in vaccination against certain diseases and pathogens; however, vaccines are not yet available for many important diseases. Science and research into vaccination is progressing well and there is hope that more vaccines will be available in the coming years.
The Use of Veterinary Drugs and Vaccines in Mediterranean Aquaculture, 2003/05/21-23, Izmir (Turkey)